Environmental and health implications of Pb-bearing particles in settled urban dust from an arid city affected by Pb–Zn factory emissions - M. F. Soto-Jiménez; S. Roos-Muñoz; S. Soto-Morales; L. E. Gómez-Lizarrága; L. Bucio-Galindo (Scientific Reports, 2023)
Abstract Metal-rich particles originating from non-ferrous metallurgical activities are the primary source of atmospheric metals in urban environments. These particles vary in size, morphology, and elemental compositions and they undergo weathering processes that alter their composition and affect their toxicity. This study focuses on lead (Pb)-rich particles in settled urban dust within an arid and dusty city, Torreón in North Mexico, affected by Met–Mex Peñoles complex, one of the world's largest Ag–Cd–Pb–Zn smelting and refining facilities in operating since 1901. Torreón is characterized by arid conditions, temperature fluctuations, and low humidity. Dry atmospheric particles were collected in 2015 and 2017 from Torreón's urban area within a 3 km radius of the Met–Mex Peñoles complex. We used various analytical techniques, including scanning electron microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), and X-ray powder diffraction (XRD) to determine the size, morphology, elemental composition and mineralogy of Pb-bearing particles. Our analysis revealed a range of Pb-bearing particle sizes and morphologies with varying Pb (0.3 to 51–87.2%) and other element contents, such as As (0.04 to 1–3.4%), Cd (0.4 to 3.3–5.1%), Cu (0.51–14.1%), Hg (ND-0.6%), and Zn (1.7 to 79–90.3%). XRD analysis confirmed the presence of Pb and Zn sulfides, Pb carbonates, Pb sulfate, and Pb oxides in urban dust, both as individual particles and agglomerates. Primary Pb minerals were linked to fugitive feed concentrates and smelter flue gas at Met–Mex Peñoles, while secondary Pb minerals, like Pb carbonates, Pb sulfate, and Pb oxides, resulted from direct emissions and weathering processes. Compared to galena, secondary Pb minerals exhibit higher chemical availability in the environment, posing greater risks to the environment and human health. As the particles analyzed are presumed to be resuspended rather than freshly emitted by Met–Mex, the presence of secondary Pb minerals in settled urban dust is predominantly linked to weathering processes. The physical and chemical transformations in Pb-rich particles contribute to increased Pb bioavailability and toxicity in urban dust, with substantial implications for environmental and human health. These findings highlight the potential consequences of weathered Pb-rich particle in urban areas, particularly in the arid and dusty city of Torreón.